The calculus of violence : how Americans fought the Civil War - Sheehan-Dean, Aaron Charles (Harvard University Press, 2018)
Discarding tidy abstractions about the conduct of war, Aaron Sheehan-Dean shows that the notoriously bloody US Civil War could have been much worse. Despite agonizing debates over Just War and careful differentiation among victims, Americans could not avoid living with the contradictions inherent in a conflict that was both violent and restrained.--